STUDI POTENSI PERTANIAN “KAKI“ LAWU SELATAN WILAYAH WONOGIRI - Arief Budi Nugroho; Eko Murniyanto (Universitas Trunojoyo Madura, 2014)
Agricultural potential have the highest contribution to Gross Domestic Product Wonogiri (BPS, 2011) because it is proper database agricultural potential is necessary for basic agricultural development planning in particular and the economy in general. In turn can be achieved high revenue. This study aims to provide information on the potential of agriculture in the